Protein levels for bulls on 140-day, gain test - McKee, M.; Schalles, R.R.; Zoellner, K.O. (Kansas State University. Agricultural Experiment Station, 2011)
Three trials with Angus, Hereford, and Shorthorn bulls produced in the University teaching herd were conducted to determine effects of 10, 12, or 14% calculated crude protein levels in grain rations. In trial 1, the 10% crude protein grain rations resulted in significantly (P<.0l) lower gains than did either 12 or 14% crude protein grain rations. The 10% ration was not tested in trials 2 and 3. Rates of gain and feed per pound of gain did not differ significantly between bulls fed 12% or 14% protein rations.
Keywords: Beef; Protein; Gain